Corneal confocal microscopy demonstrates minimal evidence of distal neuropathy in children with celiac disease - Hoda Gad (6470522) (2020)
Objectives The aim of this study was to utilise corneal confocal microscopy to quantify corneal nerve morphology and establish the presence of sub-clinical small fibre damage and peripheral neuropathy in children with celiac disease. Methods This is a cross-sectional cohort study of twenty children with celiac disease and 20 healthy controls who underwent clinical and laboratory assessments and corneal confocal microscopy. Corneal nerve fiber density (no.mm2), corneal nerve branch density (no.mm2), corneal nerve fiber length (mm.mm2), corneal nerve fiber tortuosity and inferior whorl length (mm.mm2) were quantified manually. Results Corneal nerve fiber density (34.7±8.6 vs. 32.9±8.6; P = 0.5), corneal nerve branch density (47.2±24.5 vs. 47.3±20.0; P = 0.1) and corneal nerve fiber length (20.0±5.1 vs. 19.5±4.5; P = 0.8) did not differ between children with celiac disease and healthy controls. Corneal nerve fiber tortuosity (11.4±1.9 vs 13.5±3.0; P = 0.01) was significantly lower and inferior whorl length (20.0±5.5 vs 23.0±3.8; P = 0.06) showed a non-significant reduction in children with celiac disease compared to healthy controls. Inferior whorl length correlated significantly with corneal nerve fiber density (P = 0.005), corneal nerve branch density (P = 0.04), and corneal nerve fiber length (P = 0.002). Conclusion Corneal confocal microscopy demonstrates minimal evidence of neuropathy in children with celiac disease. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0238859